Mathematics PISA Problems Using Local Context for Elementary School Students - Agus Susanta; Irwan Koto; Edi Susanto (Universitas Maritim Raja Ali Haji, 2023)
Referring to the results of an international survey, one of which is PISA, the achievements of Indonesian students are still below the global average score. The main problem that is the causative factor is that students need to be used to solving similar problems. The issues used in PISA questions are familiar to only some students in Indonesia. This study aimed to develop PISA model mathematical problems with valid and reliable local contexts and potential impacts. The type of research conducted is development research using the ADDIE model with the stages of analysis, design, development, and evaluation. The test subjects were fifth-grade elementary school students in Bengkulu and South Sumatra provinces. The research instruments were product development validity sheets, legibility sheets, and student response questionnaires. Data analysis consisted of validity analysis using the Aiken Index and reliability with Cronbach Alpha. The study results show that PISA model mathematical questions with the regional context meet the validity, reliability, and potential impact criteria. The results of the implementation test showed that 11 students (27.50%) were in the low category, 32 students (55.00%), and 7 students (17.50%) were in the high category.